2010
DOI: 10.1007/s13238-010-0095-x
|View full text |Cite
|
Sign up to set email alerts
|

Mice-lacking LMP2, immuno-proteasome subunit, as an animal model of spontaneous uterine leiomyosarcoma

Abstract: Uterine tumors are the most common type of gynecologic neoplasm. Uterine leiomyosarcoma (LMS) is rare, accounting for 2% to 5% of tumors of the uterine body. Uterine LMS develops more often in the muscle tissue layer of the uterine body than in the uterine cervix. The development of gynecologic tumors is often correlated with female hormone secretion; however, the development of uterine LMS is not substantially correlated with hormonal conditions, and the risk factors are not yet known. Radiographic evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Strong expression of cyclin E and Ki-67, biomarker candidates for malignant mesenchymal tumors, was also observed in the uterine leiomyosarcoma and uterine tumors (Figure 1, Figure 2). Previous studies have indicated that the spontaneous onset of uterine leiomyosarcoma is observed in LMP2/β1i-deficient mice, which is one of the subunits of the immunoproteasome (12,13). In human uterine leiomyosarcoma, the expression of LMP2/β1i is significantly reduced (12,13,14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strong expression of cyclin E and Ki-67, biomarker candidates for malignant mesenchymal tumors, was also observed in the uterine leiomyosarcoma and uterine tumors (Figure 1, Figure 2). Previous studies have indicated that the spontaneous onset of uterine leiomyosarcoma is observed in LMP2/β1i-deficient mice, which is one of the subunits of the immunoproteasome (12,13). In human uterine leiomyosarcoma, the expression of LMP2/β1i is significantly reduced (12,13,14).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research studies have indicated that the spontaneous onset of uterine leiomyosarcoma is observed in mice lacking LMP2/β1i, which is a subunit of the immunoproteasome (12,13,14). In human uterine leiomyosarcoma, the expression of LMP2/β1i is significantly reduced (12,13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, BCl-2 is underexpressed [51]. Furthermore, experimentally, using knockout mice models, the potential of BRCA1 in formation of leiomyosarcoma [52] was proven or lack of the LMP2 gene probably spontaneously develops this disease [53].…”
Section: Mesenchymal Tumorsmentioning
confidence: 99%
“…Although many genes and signaling pathways have been identified to improve detection and treatment of LMS, surgical removal of tumors is currently the most effective way to treat leiomyosarcoma. Poor prognosis of LMS is related to a higher degree of malignancy, larger tumor volume, and deeper tumor site (Hayashi et al, 2010;Ognjanovic et al, 2012;Croce and Chibon, 2015). Therefore, identification of new biomarkers to assess malignancy and prognosis of LMS is essential.…”
Section: Introductionmentioning
confidence: 99%